Pressure drop analysis for optimum inside-casing gravel pack design - Tan, Czek Hoong (2004)
A computer simulation program is developed to evaluate the productivity of inside-casing gravel packs. The assumptions are that perforations are treated as small wedges and gravel is assumed to fill the perforation and the casing-screen annulus. A three-dimensional, finite-difference model is developed that is capable of modeling the flow pattern in the multiple perforation system. The high-velocity effects are accounted for by the Forchheimer equation. The pressure drop across the annular gravel pack is calculated based on the skin factor. The simulator was successfully validated against pressure drop data of actual gravel-packed wells. The resulting package can be used to study the effect of gravel-packed well parameters on overall productivity. The well parameters studied are perforation length, diameter, density, angle, pattern, gravel permeability and flow rate.